To tell or not to tell the diagnosis of schizophrenia. Issue 1 (March 1989) - Atkinson, J M
Abstract : Some patients with schizophrenia are not told their diagnosis. The moral, clinical and practical issues involved in telling or not telling the patient are discussed. In some cases a relative is told the diagnosis but not the patient. The implications for the family and clinical outcome are outlined. A case history illustrating some of these issues is presented.